Physical activity levels of 6th graders at the International School of Lusaka and Kapwelyomba Primary School - Kamangu, Musonda E. (Lusaka: University of Zambia , School of Medicine, 2016)
Childrens higher level of actvity are known to contribute to the developmental outcomes for a healthy lifestyle. Non communicable diseases are a leading cause of death globally, sub Saharan Africa is projected to have largest numbers of victims of non communicable diseases death. Children of today are reported to be slowly adapting a sedentary life style thereby increasing the risk of developing non communicable diseases. The study attempted to examine differences in physical activity levels between 6 th graders at International School of Lusaka and Kapwelyomba Primary School.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Physiotherapy.
Includes bibliographical references.
Keywords: Motor ability in children; Physical fitness for children